2007
DOI: 10.1093/jxb/erm012
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis reveals differences between Vitis vinifera L. cv. Chardonnay and cv. Cabernet Sauvignon and their responses to water deficit and salinity

Abstract: The impact of water deficit and salt stress on two important wine grape cultivars, Chardonnay and Cabernet Sauvignon, was investigated. Plants were exposed to increasing salinity and water deficit stress over a 16 d time period. Measurements of stem water potentials, and shoot and leaf lengths indicated that Chardonnay was more tolerant to these stresses than Cabernet Sauvignon. Shoot tips were harvested every 8 d for proteomic analysis using a trichloroacetic acid/acetone extraction protocol and two-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
156
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(162 citation statements)
references
References 101 publications
6
156
0
Order By: Relevance
“…Two ribosomal proteins, 40S RPS27 and 60S RPL27, were up regulated under desiccation stress (Table 1, Figure 5). Vincent et al (2007) have reported that in grapevine shoots, there is an increased abundance of RPL39 in response to drought. In yeast, this protein is a 60S ribosomal subunit implicated in translational accuracy (Dresios et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Two ribosomal proteins, 40S RPS27 and 60S RPL27, were up regulated under desiccation stress (Table 1, Figure 5). Vincent et al (2007) have reported that in grapevine shoots, there is an increased abundance of RPL39 in response to drought. In yeast, this protein is a 60S ribosomal subunit implicated in translational accuracy (Dresios et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we investigated other phenotypes than growth. Based on the other previous studies that suggested the involvement of plant TCTP in abiotic stress signaling such as water deficit (Vincent et al, 2007), we investigated drought stress responses and found significantly enhanced drought tolerance in the AtTCTP overexpression plants (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been reported that plant TCTP shows increased expressional levels in response to water and osmotic stress (Ermolayev et al, 2003;Vincent et al, 2007), we performed the expression analysis of AtTCTP in the presence of ABA using the transgenic plants carrying AtTCTP pro :GUS construct. The results showed that GUS expression was detected in whole roots of transgenic seedlings with AtTCTP pro :GUS in the presence of ABA, whereas that was detected only in root apical meristem in the absence of ABA (Supplementary Fig.…”
Section: Overexpression Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…TCTP is also an important participant of the TOR-pathway, a nutrition sensor and growth regulator in different organisms (Deprost et al, 2007;Brioudes et al, 2010). Its regulation was detected during salinity stress in plants and bacteria (Vincent et al, 2007;Santa Brígida et al, 2014). TCTP proved to be down-regulated during mild salinity stress in both Littorina species.…”
Section: Discussionmentioning
confidence: 99%